Identification and functional characterization of RIPK3-binding protein in necroptosis - 박한희 (The Graduate School, Ajou University, 2022)
Necroptosis is a type of programmed cell death induced by various stress signals, such as the tumor necrosis factor (TNF) family, Toll-like receptor (TLR), interferons (IFNs), or lipopolysaccharide (LPS). Such stimuli cause the formation of necrosome complex containing receptor interaction protein kinases 1, 3 (RIPK1, RIPK3) and mixed lineage kinase domain-like (MLKL), which is essential for death to proceed. RIPK3-dependent plasma membrane localization of MLKL is necessary for necroptosis, and leads to plasma membrane disruption. In addition to MLKL, it has been identified several metabolic enzymes in screening for interactions with RIPK3 but there are not many proteins are identified. In my study, I conducted two approaches to identify novel binding partner of RIPK3. In proteome microarrays, I found that pellino E3 ubiquitin protein ligase 1 (PELI1) as a novel direct binding partner of RIPK3. PELI1 targets RIPK3 protein for proteasome-dependent degradation. I identified RIPK3 K363 as the main target for PELI1-mediated ubiquitylation by mass spectrometric analysis. PELI1 associates with, and then preferentially target, kinase-active RIPK3. Further investigation revealed that phosphorylation of RIPK3 on T182, which only occurs in kinase-active RIPK3 leads to interaction with the FHA (forkhead associated) domain of PELI1. PELI1-mediated RIPK3 degradation effectively prevents cell death triggered by RIPK3 hyperactivation. Importantly, upregulated RIPK3 expression in keratinocytes from toxic epidermal necrolysis (TEN) patients is correlated with low expression of PELI1, suggesting that loss of PELI1 may play a role in the pathogenesis of TEN. So, I propose that PELI1 may function to control the inadvertent activation of RIPK3, thus preventing aberrant cell death and maintaining cellular homeostasis. Next, in Tandem-affinity purification linked to mass spectrometry (TAP-MASS) analysis, I found Tripartite Motif Protein 28 (TRIM28) as a RIPK3 interacting protein. The co-repressor function of TRIM28 have been shown recently to be linked to the development of various cancers, such as non-small cell lung cancer, breast cancer, cervical cancer, colon cancer, gastric cancer, and ovarian cancer. In this study, I found that TRIM28 is a negative transcriptional regulator that is itself negatively regulated when cells undergoing necroptosis continue de novo synthesis of immunostimulatory cytokines. TRIM28 antagonizes NF-κB transactivation independent of p65 chromatin occupancy, but RIPK3 activation-mediated phosphorylation of TRIM28 at serine 473 facilitates its derepression. Moreover, RIPK3 activation triggers a remarkable reduction in TRIM28 binding events in chromatin that leads to increased other transcriptional factor activity, such as SOX9. These results revealed a new necroptosis-mediated transcription circuit that is modulated by RIPK3 activation-dependent de-repression of TRIM28, which provides a mechanism to promote robust anti-tumor immunity and contributes to tumor immunogenicity.
학위논문(박사)--아주대학교 일반대학원 :의생명과학과,2022. 2
Keywords: Necroptosis; PELI1; RIPK3; TRIM28 and immunogenic cell death (ICD); proteasomal degradation